Planting a New Church Through Education in the Abun Sausapor Tribe, Tambrauw Regency, West Papua - Denny Ferdinand Mamuli (International Journal of Education, Information Technology, and Others, 2026)
In the life of the church members, today many have advanced socially, economically and educationally compared to the church members in the land of Abun Regency, Tambrauw, West Papua which is in the mountains so that there is a wall separating the order of life. Likewise with the Abun Tribe in Sausapor, Tambrauw Regency, they switched to Islam after previously only adhering to animism. And this separation wall makes it difficult for God's people who are advancing in reaching the Abun tribe in Tambrauw Regency, West Papua. With this, the church goes through several approaches to the local community in carrying out the mission of Allah and planting a new church, namely how to reach the Abun tribe community through Education. The Church can grow but it needs those who are willing to give themselves earnestly to that highest calling. Above all, the strategic ability that is the cause of the growth of a church is due to the power of the Holy Spirit. There are various methods of church growth through evangelism and one of them is through formal educational means, namely schools organized by the church, and schools can also be used as a means and strategies for church growth and planting. Furthermore, the students in the church-run school are a wonderful mission field for church planting. From this mission of church planting through education, the church seeks to manage a school, organize branches of the Sabbath School and enter new territory. And build churches in the places of the Sabbath school branches. And there are many evangelistic activities carried out so that many souls are baptized